Hubungan Tingkat Pengetahuan dengan Partisipasi Vaksinasi COVID-19 di Puskesmas Betun Kabupaten Malaka - Kehi Lau, Cindy Anna Maria; Koamesah, Sangguana Marthen Jacobus; Sagita, Sidarta; ningsih, Iswa (Universitas Nusa Cendana, 2022)
Background : The Corona Virus Disease 2019 pandemic is a health problem that is currently in the world's spotlight. COVID-19 has been designated by the Indonesian government as a non-natural disaster and has received attention from health scientists and the general public. Since January 2021, the government has carried out vaccinations in stages while remaining disciplined in health protocols. Evaluation of effectiveness proves that vaccines are able to reduce the risk of being infected with COVID-19, as well as reduce treatment and death for the residents. COVID-19 vaccination aims to reduce the transmission of COVID-19 between the residents and is expected to achieve herd immunity. Public knowledge of COVID-19 and vaccines can support the success of this disease management program. Based on the results of a vaccine acceptance survey conducted by the Ministry of Health, ITAGI, UNICEF and WHO, around 30% of their respondents expressed concerns about the safety and effectiveness of vaccines, expressed distrust of vaccines, and questioned the halalness of vaccines because the coverage of vaccine information provision in Indonesia has not been maximized because it is still new and there are mutations from the coronavirus. Objective : This study aims to determine whether there is a relationship between the level of knowledge and the participation of COVID-19 vaccination at the Betun Health Center, Malaka Regency. Method : This study used an analytical observational research design with a cross sectional design. Samples were choosen using a non-probability sampling technique with a type of consecutive sampling with a total sample of 100 people. The data were collected using a questionnaire on Knowledge of COVID-19 Vaccination Participation to the visitors of Betun Health Center, Malaka Regency. The data analysis used is the Chi-Square test. Result : From the test results using the chi-square test, there was a significant correlation between the level of knowledge with the participation of COVID-19 vaccination at the Betun Health Center, Malaka Regency with the p value = 0.005. Conclusion : There is a significant correlation between the level of knowledge with the participation of COVID-19 vaccination at the Betun Health Center, Malaka Regency. Keywords : Level of knowledge, participation, vaccination